Gambaran Penggunaan Antibiotik Profilaksis pada Pasien Bedah Appendicitis di Rumah Sakit Arun Lhokseumawe Tahun 2020-2022 - Khaira Maulina; Anna Millizia; Yuziani Yuziani (Inovasi Kesehatan Global, 2025)
Appendicitis is a common health problem in Indonesia. Appendicitis requires surgery because it's an acute inflammation. Appendicitis can be treated with surgery to remove the appendix, namely appendectomy, by performing surgery on the abdominal tract. Appendectomy is a clean-contaminated surgery that can cause surgical wound infection in around 5-15% of cases. Prophylactic antibiotics are included in infection prevention. It is important to evaluate the use of prophylactic antibiotics in appendicitis surgery patients to reduce drug side effects and prevent surgical site infections. Infections can be caused by microorganisms such as pathogenic bacteria, and antibiotics are the most commonly used drugs to treat such infections. SSI can cause morbidity, mortality, increased length of stay, and increased patient care costs. The researchers chose Arun Lhokseumawe Hospital as the research site because no research had ever been conducted at Arun Lhokseumawe Hospital on the use of prophylactic antibiotics in appendicitis surgery patients. Preliminary survey results based on Arun Lhokseumawe Hospital medical records from 2020 to 2022 showed that 202 patients underwent surgery. The purpose of this study was to determine the profile of prophylactic antibiotic use in appendicitis surgery patients using the Gyssens method at Arun Lhokseumawe Hospital from 2020 to 2022. This study was observational in nature, using total sampling as the sampling technique. The Results of the study showed that the most frequently used type of prophylactic antibiotic was Cefotaxime (53.5%) and the appropriateness of antibiotic use was category 0 (97%) because it was appropriate and category IVA (3%) because there were other antibiotics that were more effective. It can be concluded that Cefotaxime is the most frequently used antibiotic, and the appropriateness of prophylactic antibiotics at Arun Hospital in Lhokseumawe City is already appropriate.